Adoption of Integrated Crop Management Technology Innovation and Sustainable Lowland Rice Development Strategy in Tasikmalaya Regency, West Java Province - Abdul Mutolib; Candra Nuraini; Kirana Nur Ilmiati (The University of Lampung, 2026)
Adoption of Integrated Crop Management (ICM) technology affects both productivity and the sustainability of farming practices. This study aims to analyze the level of ICM adoption, identify influencing factors, and formulate strategies for sustainable rice cultivation. The research employed a quantitative approach using a survey of 76 rice farmers in Salawu District, Tasikmalaya Regency. Adoption levels were assessed based on 11 key indicators. Factors influencing adoption were examined using multiple linear regression with F-test for simultaneous significance and t-test for partial effects. SWOT analysis was employed to develop rice cultivation strategies. The results indicate that the overall ICM adoption level is low. Indicators with high adoption include the use of superior seed varieties, organic fertilizers, intermittent irrigation, integrated weed and pest management (IPM), and post-harvest handling. Eight significant variables were identified: land size, self-efficacy, formal education, cosmopolitan orientation, productivity, extension worker role, availability of farming inputs, and innovativeness. SWOT analysis places the adoption condition in quadrant I (aggressive strategy), emphasizing the optimization of internal strengths, strengthening agricultural extension, and diversifying simple innovations aligned with traditional practices. Participatory extension, target determinants of adoption, and support simple sustainable ICM innovations need to be strengthen to increase rice production.